(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Adaptation or natural acclimatization results from the interaction between genetic variations and acclimatization resulting in individuals with ability to live and reproduce without problems at high altitudes. Testosterone is a hormone that increases erythropoiesis and inhibits ventilation. It could therefore, be associated to the adaptation to high altitudes. Excessive erythrocytosis, which in turn will develop chronic mountain sickness is caused by low arterial oxygen saturation and ventilatory inefficiency and blunted ventilatory response to hypoxia. Testosterone is elevated in natives at high altitude with excessive erythrocytosis (>21 g /dl hemoglobin in men and >19 g/dl in women). Natives from the Peruvian central Andes with chronic mountain sickness express gene SENP1 that enhances the activity of the androgen receptor. Results of the current investigations suggest that increase in serum testosterone and hemoglobin is not adequate for adaptation to high altitude.